Disciplinary Procedures for Judges: A Case Study of the Independence of the Jordanian Judiciary Law - Momen Nayef Ahmed Al-Sa'aida; Mohammad Abdul Muhsin bin Tareef; Mohannad Azmi Abo-Moghli (European Scientific Journal, ESJ, 2019)
This paper focuses on highlighting the importance of judges’ disciplinary procedures in the light of the law of the independence of the Jordanian judiciary as the supreme organ of the state. It also shows the role of the judiciary in adjudicating disputes between individuals or between individuals and the State in terms of its autonomy, independence of judicial supervision, and judicial immunity, as well as the disciplinary procedures. The following was discussed: concept of discipline and the adequacy of the disciplinary decision, the nature of the mistakes of judicial discipline, or disciplinary sanctions. The discipline of the public servant focuses on preserving the public right, respecting the reputation of public utilities, and building functional behavior that perpetuates the work of these facilities. The aim of disciplining judges is to focus on the administration of justice. The integrity of Judges makes the State a state of law. Through this way, the judicial process and disciplinary sanctions against those who violate the right and justice of judges do not in any way interfere with the independence and prestige of the judiciary in the society. It isstated that the existence of the same penalty in the law of the independence of the judiciary and in the Jordanian civil service system does not affect the essence of the independence of the judiciary. The penalty in its name shows one, but the implementation and importance in the law of the independence of the judiciary is different from that in the civil service system.